PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA MATA PELAJARAN IPS KELAS IV SEKOLAH DASAR - Ika Silvi Anisa; Arie Widya Murni (ELENOR: Elementary School Journal, 2024)
The development of learning media in the form of a website that will be used by fourth grade elementary school students in social science lessons is the aim of this research. This research uses Thiagarajan's 4D research model with 4 stages, namely the definition stage, design stage, development stage and desiminate trial stage. However, in this research, there were only 3 stages, namely definition, design stage, and development stage. The data collection instruments used were validation results sheets and interview results sheets. The website media or learning media that has been developed by this researcher has been declared suitable for use by validators, both media and material. The percentage obtained by researchers in the media expert validation results was 73% or according to these criteria, it was declared worthy of development by researchers. The percentage of results obtained by researchers from material expert validation was 88%, which is included in the criteria for being very suitable for development in this research